2008
DOI: 10.1016/j.visres.2008.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of artificial vision: IV. Visual information required to achieve simple pointing and manipulation tasks

Abstract: Retinal prostheses attempt to restore some amount of vision to totally blind patients. Vision evoked this way will be however severely constrained because of several factors (e.g., size of the implanted device, number of stimulating contacts, etc.). We used simulations of artificial vision to study how such restrictions of the amount of visual information provided would affect performance on simple pointing and manipulation tasks. Five normal subjects participated in the study. Two tasks were used: pointing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 42 publications
1
28
1
1
Order By: Relevance
“…5 Since then, multiple studies conducted during long-term clinical trials of retinal prostheses have demonstrated that these devices can, indeed, provide some benefit in the realms of visual acuity, 6 object and letter recognition, 7,8 and orientation and mobility. 3 Research into hand-eye (or hand-visual prosthesis) coordination for subjects with retinal prostheses, however, is confined mostly to simulations [9][10][11][12][13] and pointing tasks. 3 As demonstrated by Humayun et al, prostheses with at most 60 functioning electrodes are sufficient to improve the pointing ability of blind patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 Since then, multiple studies conducted during long-term clinical trials of retinal prostheses have demonstrated that these devices can, indeed, provide some benefit in the realms of visual acuity, 6 object and letter recognition, 7,8 and orientation and mobility. 3 Research into hand-eye (or hand-visual prosthesis) coordination for subjects with retinal prostheses, however, is confined mostly to simulations [9][10][11][12][13] and pointing tasks. 3 As demonstrated by Humayun et al, prostheses with at most 60 functioning electrodes are sufficient to improve the pointing ability of blind patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have studied simulated prosthetic vision in normal sighted subjects using limited and different low resolution pixelated images . There is a large variety of visual phosphene profiles described in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Chai et al explored minimum requirements for efficient recognition of pixilated Chinese characters and reported that recognition accuracy could be optimal with at least 12 × 12 pixels. Perez Fornos et al studied how the restrictions of visual information would affect performance on simple pointing and manipulation tasks. Their results demonstrated that accuracy was close to normal under high‐resolution conditions and decreased at 500 pixels or below, depending on the field of view used.…”
mentioning
confidence: 99%
“…Our main purpose was to determine the upper limit (best possible) reading performance attainable with such a device, by assuming that all the information delivered by the implant reaches the brain (i.e., that there is no loss and/or distortion of the “electric image” at the electrode-nerve interface). In addition, our previous studies examining eye–hand coordination and mobility tasks (Perez Fornos, 2006; Perez Fornos et al, 2008) revealed that each task has different requirements in terms of spatial resolution or magnification (“zoom”). In other words, not only the actual number of points or pixels available to decode the image but also the content of the image (effective visual field size) represented by these pixels is crucial to achieve the best possible performance for each task.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has conducted a series of studies aimed at determining the visual information required to perform a variety of tasks under such restricted viewing conditions. They were based on computer simulations carried out on subjects with normal vision (Sommerhalder et al, 2003, 2004; Perez Fornos et al, 2005, 2008; Pelizzone et al, 2006; Perez Fornos, 2006). These experiments demonstrated that about 500 distinct phosphenes, distributed on a 10° × 7° central retinal area could restore significant reading abilities to blind patients (i.e., reading accuracy >95% and reading rates of 60–75 words/min).…”
Section: Introductionmentioning
confidence: 99%